2023
DOI: 10.1039/d3cp01070h
|View full text |Cite
|
Sign up to set email alerts
|

Description of quantum interference using mixed quantum/classical theory of inelastic scattering

Abstract: Quantum oscillations of total scattering cross section in the N2 + O system are well reproduced by MOLSCAT and MQCT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…To date, numerous studies concerning the PESs of the H 3 + system have shown the presence of an CI between the ground state and the first excited state at reactant Jacobi distance R greater than about 7 bohr. This CI seam was found to interfere with the photodissociation of H 3 + and play a crucial role in the CT process, while the effect on the ground-state reaction is unknown. Moreover, the study of the quantum interference effect in chemical reactions is helpful in understanding the chemical reaction process more deeply. In this work, we examined the role of the nonadiabatic effect in the D + + H 2 reaction and discussed the influence of the quantum interference among various partial waves on the angular distribution of the products, employing the time-dependent wave packet (TDWP) approach based on an improved L-shaped grid . A set of precise diabatic PESs containing the lowest three singlet states and their couplings proposed by Aguado et al (hereafter referred to as ARS PESs) is used in the present quantum dynamics calculations.…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous studies concerning the PESs of the H 3 + system have shown the presence of an CI between the ground state and the first excited state at reactant Jacobi distance R greater than about 7 bohr. This CI seam was found to interfere with the photodissociation of H 3 + and play a crucial role in the CT process, while the effect on the ground-state reaction is unknown. Moreover, the study of the quantum interference effect in chemical reactions is helpful in understanding the chemical reaction process more deeply. In this work, we examined the role of the nonadiabatic effect in the D + + H 2 reaction and discussed the influence of the quantum interference among various partial waves on the angular distribution of the products, employing the time-dependent wave packet (TDWP) approach based on an improved L-shaped grid . A set of precise diabatic PESs containing the lowest three singlet states and their couplings proposed by Aguado et al (hereafter referred to as ARS PESs) is used in the present quantum dynamics calculations.…”
Section: Introductionmentioning
confidence: 99%
“…In this Letter we explore an alternative approach for the description of quantum effects in molecular collisions, named the mixed quantum/classical theory (MQCT). In our method the scattering process of collision partners (their translational motion) is described approximately using the mean-field Ehrenfest method, while the rotational motion of collision partners is described rigorously by solving the time-dependent Schrodinger equation, which incorporates all quantum phenomena associated with their internal states. During the past decade MQCT was applied to several molecular systems and was found to give results often comparable to the full-quantum results. ,, One important advantage of MQCT is its affordable numerical cost.…”
mentioning
confidence: 99%
“…Other details of MQCT theory, including all equations, can be found in our recent papers. 23,29,33,46 In order to gauge the accuracy of MQCT we also carried out a set of benchmark full-quantum calculations using the HIBRIDON package 47 with the same simplifying assumptions about the NO + Ar potential energy surface and the same rotational basis set, at one value of total energy E tot = 651 cm −1 with maximum value of J tot ≤ 190. A comparison of cross sections obtained by the two methods is presented in Figure 1 for six different initial states of the NO molecule with the corresponding collision energies.…”
mentioning
confidence: 99%
See 1 more Smart Citation